Envelope for letter sent to A. W. Thayer in Cambridgeport, Mass., from New York, stamped 10 October (year unknown). - Thayer, Alexander Wheelock, 1817-1897::::::::::::::: (United States, 2022)
Envelope for letter sent to A. W. Thayer in care of his brother Dr. Henry Thayer in Cambridgeport, Mass., from New York, stamped 10 October (year unknown).